PENGARUH MODERNISASI SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PENYULUHAN DAN KONSULTASI PERPAJAKAN DI KABUPATEN HULU SUNGAI UTARA PROVINSI KALIMANTAN SELATAN - Ida Mentayani; Rusmanto Rusmanto; - mail (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2015)
Abstract This study aims to provide empirical evidence about the influence of organizational restructuring, improvement of business processes through the use of communications and information technology, and the improvement of human resources on tax compliance. The population in this study is the taxpayer at the Office of Counseling and Consultation Services Tax Amuntai, Hulu Sungai Utara. The sample in this study as many as 100 people. The method used is multiple linear regression method with SPSS 20 to test the hypothesis. The results showed that the variables of organizational restructuring, and improvement of business processes through the use of information and communication technologies influence on tax compliance. While the improvement of human resource variables had no effect on tax compliance.